The Empowerment of Labour Women Picking Coffee Through the Education of Functional Literacy Based on Local Potentials - Indrianti, Deditiani Tri; Hartatik, Sri; Fajarwati, Linda (Universitas Negeri Semarang, 2020)
Women picking coffee workers have a big enough role in all lines. However, the level of education and knowledge is still relatively low. It occupies a subordinate and marginally positioned position. This research aims to find the empowerment of women’s coffee picking labourers through the process of functional literacy programs. The existence of the program is expected to improve women’s empowerment The study was designed with a qualitative approach. Researchers use two primary types of data (1) Primer, i.e. data obtained by researchers directly from speakers as informers who are directly related to the empowerment of the local potential coffee-picking labour. Primary data sources of research using interviewing techniques and observation techniques (2) secondary, are supplementary research data that will be obtained through reports in the form of learning activities, documents, and textbooks relevant to the purpose of research. Before processing, the collected primary data is checked for the validity of the data. In this case, it is used triangulation technique, to be processed and analyzed by the technique of Gender Analysis Pathway (GAP). Where the gender engineering pathway analysis is used to analyse the policy of development programs, in this case, is a functional literacy program. The results showed that there was an increase in the empowerment of female coffee picking labours through a functional literacy program based on local wisdom. Reading, writing and counting ability can realize women have an unworthy job. The re-formulation of the learning design conducted through functional literacy programmes became the main thing for working women picking coffee in recognizing local potentials designed in accordance with local characteristics. The design of attention-learning to local potentials has become a key thing in enhancing the power of women so that it can find the resources that are based in everyday life.